Hawking Space and National Policy on Urban Street Hawkers: A Study of NDMC, Delhi. (2016) - Sharma, Shweta
Abstract: National Policy on Urban Street Hawkers (NPUSV) passed in 2009 made it mandatory for all the master plans of cities/ towns to demarcate an area for hawkers to carry out their daily activities. The policy advocated that spatial planning should take into account the natural propensity of street hawkers to locate in certain places at certain times in response to the patterns of demand for their goods/services and thereby make hawking zone, restricting hawking zones and no hawking zones in cities. Quantitative space norms were mentioned whereby it was mentioned that there is a need to fix space norms for hawking at both city/zonal development plan and local/layout plan levels, but these quantitative norms were left open ended to be worked out by each city/ town. The present paper is an attempt to elaborate on quantitative norms for NDMC area of Delhi.